PENGARUH CURAH HUJAN DAN HARI HUJAN TERHADAP PRODUKSI KELAPA SAWIT BERUMUR 5, 10 DAN 15 TAHUN DI KEBUN BEGERPANG ESTATE PT.PP LONDON SUMATRA INDONESIA, Tbk - Lastiar Ningsih Simanjuntak; Rosita Sipayung; Irsal Irsal (Jurnal Agroekoteknologi, 2014)
One of the determining factors of water supply for oil palm which does not use irigation system israin fall. Water supply is the main factor that cope production rate of oil palm. Water supply for oilpalm in field is obtained from rain fall. This research is done in PT.PP London Sumatra Indonesia,Tbk Begerpang Estate plantations, North Sumatera Province, Medan from June to September 2013.This research used secondary data available in company administration. Secondary data for analysisneed consists of component production data as total bunches, average bunches weight, total ofproductive trees, loose fruit weight; production of fresh fruit bunch (FFB); rain fall data and rainday monthly in 2008, 2009 and 2010 on 6 divisions. Analysis method used is double linierregression and correlation analysis. Model tested by classic asumption consists of normality test,heteroskedasticity test, multicollinearity, and autocorellations test by using statistic softwareSPSS.v.17 for windows. The regression analysis shows that rain fall and rain day variables havesignificant influence with alpha 5% (Sig < α 0,05) in FFB production aged 5 years. F-value is5,235 with significant level 0,031. Coeffisien determination obtained is 53,8%. It means 53,8%variance of FFB production can be explained by variables used in this research and the rest 46,2% isexplained by other variables which are excluded. Linier regression model on 5 years is Y = 145,982+ 1,451 rain fall – 27,005 rain day + E. Corelation result on 5, 10 and 15 years with two-tailedanalysis with significant level 1% shows that rain fall and rain day have tight, significant, and samedirection relationship. Corelation value of rain fall and rain day are 0,892; 0,887; and 0,855 eachwith significant level 0,000 (Sig < α 0,01).Keywords: rain fall, rain day, FFB production.